KOMPOSIT DEGRADABEL POLIETILENA TEREFTALAT DENGAN SELULOSA MENGGUNAKAN REAGEN FENTON (H2O2/Fe2+) - Trimastiya, I M.; Negara, I M. S.; Ratnayani, O.; Simpen, I N. (Jurnal Kimia (Journal of Chemistry), 2019)
PET is a non-degradable type of plastic that can cause environmental problems. This study aimed to form composites by cross-linking PET with cellulose using Fenton reagent initiator, finding out the effect of the addition of H 2 O 2 on the fenton reagent used as an initiator in the mixture of PET-cellulose composites to water absorption and the rate of degradation in wet and dry soil media. The steps carried out in making PET-cellulose composites was refining PET using swelling techniques, followed by the formation of PET-cellulose composites by cross-linking through free radical reaction using fenton (H 2 O 2 /Fe 2+ ) as the initiator with the variation of H 2 O 2 amount (30 grams, 60 grams, 90 grams). The resulting composites were tested for water absorption and degradation properties in wet soil media and dry soil with untreated PET control. Characterization was carried out by functional group analysis using FTIR and its morphology with SEM. The results of the study showed that the composite making using the technique of cross-linking between polyethylene terephthalate and cellulose using fenton reagents was successfully carried out where the degradation rate of PET-cellulose composites slowed as the amount of hydrogen peroxide was used. In PET-cellulose composites, the more amount of H 2 O 2 used, the weaker the absorption of the composite to water was. Keywords: degradable, fenton (H 2 O 2 /Fe 2+ ), PET (Polyethylene Tephthalate), cellulose, composite.